Linkage Analyses of Extracellular Glucans from Streptococcus sanguis and Streptococcus mitior - Freedman, M. (Infect Immun, 1979)
Similar α-(1→6) linkage-rich, soluble, extracellular glucans have been isolated from six strains of two genetically distinct groups of Streptococcus sanguis and three strains of Streptococcus mitior.